Tính tích phân suy rộng $latex \int_{-\infty}^{+\infty} e^{-x^2} dx$

Tính tích phân suy rộng \int_{-\infty}^{+\infty} e^{-x^2} dx:

Để tính tích phân suy rộng này, ta lại đi tính tích phân sau: \int_{-\infty}^{+\infty}\int_{-\infty}^{+\infty} e^{-(x^2+y^2)} dxdy. Chú ý là \int_{-\infty}^{+\infty}\int_{-\infty}^{+\infty} e^{-(x^2+y^2)} dxdy = \int\limits_{-\infty}^{+\infty}e^{-x^2}dx \cdot \int\limits_{-\infty}^{+\infty}e^{-y^2}dy hay = (\int\limits_{-\infty}^{+\infty}e^{-x^2}dx)^2 (1)

Trước hết, ta tính tích phân \int\limits_{B_R}\int e^{-(x^2+y^2)} dxdy với B_R = \{(x,y) \in \mathbb{R}^2 | x^2 + y^2 \le R^2\}.

Đổi biến theo tọa độ cực tích phân trên: x = r\cos\varphi, y = r\sin\varphi, khi đó miền tính tích phân là B_R = \{(r,\varphi) | 0 \le r \le R, 0 \le \varphi \le 2\pi\}, và Jacobian Jac = r, từ đó có:

\int\limits_{B_R}\int e^{-(x^2+y^2)} dxdy = \int\limits_{0}^{2\pi}d\varphi\int\limits_{0}^{R}r.e^{-r^2}dr = \pi(1 - e^{-R^2}).

Do đó \int_{-\infty}^{+\infty}\int_{-\infty}^{+\infty} e^{-(x^2+y^2)} dxdy = \lim_{R \to \infty}\int\limits_{B_R}\int e^{-(x^2+y^2)} dxdy

= \lim_{R \to \infty}\pi(1 - e^{-R^2}) = \pi.(2)

Từ (1) và (2) suy ra:  \int_{-\infty}^{+\infty} e^{-x^2} dx = \sqrt{\pi}

Advertisements

Leave a Reply

Fill in your details below or click an icon to log in:

WordPress.com Logo

You are commenting using your WordPress.com account. Log Out / Change )

Twitter picture

You are commenting using your Twitter account. Log Out / Change )

Facebook photo

You are commenting using your Facebook account. Log Out / Change )

Google+ photo

You are commenting using your Google+ account. Log Out / Change )

Connecting to %s